Kamus peribahasa Melayu digital yang pertama - Supyan Hussin,; Ding, Choo Ming; Afendi Hamat,; Arba’eyah Abdul Rahman, (Universiti Kebangsaan Malaysia, 2004)
The explosion of information and broadening of borderless world demand the Malay World to move equally fast using information communication and technology, so that the Malay World is relevant with the current context. Digital materials on the Malay World and in the Malay language in the cyber world is yet to be proud of. The Institute of the Malay World and Civilization was proactive to research, compile and reorganize Malay proverbs, and later offer a digital dictionary of Malay proverbs that can be accessed in the cyber world at http://www.atma.ukm.my or www.atma.ukm.my. Currently, basing on a research project, sponsored by UKM, ATMA has successfully developed a search engine for this digital dictionary on Malay proverbs, which consist of 19,790 entries. The system, which takes into account users’ and researchers’ needs, offers an easy search feature that is unavailable in printed media. Normally, proverbs are arranged in an alphabetical order; but this sequential format makes it difficult for users to look for specific proverbs or the meaning of the proverbs quickly. The search process is even more difficult if users do not know whether there are other proverbs that carry the same meaning, and users may become more confused when one proverb carries two different meanings. Till today, there has never been any comprehensive and friendly system ever used to access specific proverb or the meaning of the proverb. This paper will discuss the development of the first digital dictionary of Malay proverbs